LIE. ráižyti (-o) „pjaustyti, karpyti į dalis“ - Karaliūnas, Simas (Baltistica, 1982)
Lith. ráižyti (-o) “carve, engrave, cut out”The verb has probably nothing to do with rė́žti (-ia) “cut” etymologically as is sometimes supposed, but it evidently contains a root reiž- / riž-, which is represented also by Lith. pa-ráižti (-ia) “fill up”, Latv. rìẽzt (-žu, -zu) “cut, slice”, riezis “boundary, bound; patch, lot”, Lith. ryžė̃ “patch, lot, plot”, ryželis “strip, stripe”, pa-raĩžiuo. pa-reĩžiuo “in turn, in succession, in order” and others.
Keywords: lietuvių; etimologija; raižyti